Diabetes Medication Assistance Service: The pharmacist's role in supporting patient self-management of type 2 diabetes (T2DM) in Australia - Mitchell, B.; Armour, C.; Lee, M.; Song, Y.; Stewart, K.; Peterson, G.; Hughes, Jeffery; Smith, L.; Krass, I. (Elsevier Ireland Ltd, 2011)
Objective. To evaluate the capacity and effectiveness of trained community pharmacists in delivering the Diabetes Medication Assistance Service (DMAS) via (1) number and types of self-management support interventions (SMSIs); (2) number of goals set and attained by patients and (3) patient outcomes (glycaemic control, medication adherence and satisfaction). Methods. Pharmacists (n = 109) from 90 community pharmacies in Australia were trained and credentialed to deliver the DMAS. The training focused on developing pharmacists’ knowledge and skills in supporting patients’ diabetes self-management. Results. A total of 387 patients completed the trial. The mean number of SMSIs per patient was 35 (SD ±31) and the majority (87%) had at least one documented goal that was fully or partially attained. There were significant health benefits for patients including improved glycaemic control and a reduced risk of non-adherence to medications. Over 90% of DMAS patients reported improvements in their knowledge about diabetes self-management.Conclusion. The DMAS provides self management support in the community pharmacy for people with T2DM which may result in improved clinical outcomes. Practice implication. Given appropriate training in diabetes care and behavior change strategies, community pharmacists can offer programs which provide self-management support to their patients with T2DM and improve their health outcomes.